Essentials of human resource management - Somannagari, Balkishan
This book on Essentials of Human Resource Management title provides students with the technical background needed to be a knowledgeable consumer of human resource (HR) products and services, to manage HR effectively, or to be a successful HR professional. While clearly strategic in nature, the text also emphasizes how managers can more effectively acquire, develop, compensate, and manage the internal and external environment that relates to the management of human resources. It covers all aspects of human resource management and its impact on both individuals and organizations. The text builds on a foundation of research and theory, taking a practical approach focusing on critical issues and successful practices. The Highlights in HRM examples provide exact illustrations of organizational practices and policies. Important issues and critical trends are spotlighted in each chapter and reflected in the comprehensive and chapter ending cases included in the text.